Kuhn’s Incommensurability Thesis: Good Examples Still to Be Found - Prelević, Duško (Filozofia Nauki, 2019)
In The Structure of Scientific Revolutions, Thomas Kuhn famously argued that scientific revolutions consist in paradigm shifts in which the superseded and the new paradigms are incommensurable. My aim in this paper is to show that neither Kuhn’s examples nor Yafeng Shan’s recently proposed example adequately support this incommensurability thesis. Starting from the distinction between global and local incommensurability, I argue that, on the one hand, local incommensurability does not imply that paradigms are globally incommensurable, and, on the other, that it is likely that real support for Kuhn’s thesis that “the proponents of competing paradigms practice their trades in different worlds” requires global incommensurabilities. Thus, I argue that the Kuhnian view is not capable of providing satisfactory evidence that those incommensurabilities ever occurred in the history of science.